Neutrophil-to-lymphocyte ratio; platelet-to-lymphocyte ratio; systemic immune-inflammatory Index: inflammatory indicators of cognitive impairment in schizophrenia patients - Chen, Ke; Wang, Lina; Ning, Houmei; Pan, Huiqing; Zhang, Weibo (Frontiers in Psychiatry, 2025)
ObjectiveThe present study sought to evaluate the correlation between cognitive impairment (CI) and inflammatory indicators such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammatory index (SII) in schizophrenia patients.MethodsThis study included 331 schizophrenia inpatients. General data and laboratory findings (neutrophil, lymphocyte, platelet, etc.) were gathered, and then calculating NLR, PLR, and SII. A Chinese version of the Mini Mental State Examination (MMSE) was used for the assessment of cognitive function, and then the patients in the CI group were categorized into mild CI, moderate CI, and severe CI groups. Comparing the differences in NLR, PLR, and SII between the CN group and the CI group, as well as different CI groups, and analyzing the relationship between the NLR, PLR, and SII and the mechanism of CI in schizophrenia.ResultsThere were 145 (43.8%) patients with cognitive impairment. Compared to the CN group, the CI group had higher NLR, PLR, and SII than the CN group, although their lymphocyte was lower. The NLR and SII were higher in the moderate CI group than in the mild CI group. NLR, PLR, and SII were significantly inversely correlated with the total score of cognitive function and scores across all aspects, whereas lymphocytes were considerably positively correlated. Higher NLR, PLR, and SII were substantially related to an increased risk of CI, but higher lymphocytes were associated with a decreased risk of CI.ConclusionNLR, PLR, and SII may be serum inflammatory markers of CI in schizophrenia, and lymphocytes may be protective variables for cognitive function in schizophrenia.